Cerita Anak Berbahasa Sunda Tentang Aksara Kaganga sebagai Bahan Pembelajaran Menulis Siswa SD - Anjani, Firda; Kusdiana, Aan (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
Sundanese script is one of the learning topics in the fifth grade of elementary school, which learns about Sundanese script forms. In the process of learning and remembering this Sundanese script, students experience some difficulties, such as difficulty in memorizing and recalling the Sundanese script itself. This study aimed to make teachers and students more comfortable to remember and learn the process of learning Sundanese characters by illustrating the form of characters through simple conversations by grouping Sundanese characters based on the shape of the letters and the placement of the letters in the form of stories. This study used the DBR (Design-Based Research) method by research procedures of identifying learning needs, developing prototypes, testing, and reflecting. Data collection techniques were carried out through interviews and questionnaires. The research subjects were teachers and fifth-grade students of SD Negeri 3 Mangunreja, SDN Cikadu, and SD IT Al-Hikmah. The test results showed that the Sundanese language story about writing Sundanese script was appropriate and eligible as a writing learning material to be used to support the learning process. The result of this research was to produce a story in Sundanese language about the writing of the Sundanese Kaganga script as writing material for elementary school students, entitled "Tili Nulis Aksara Sunda"